(untitled) (Research, Society and Development, 2020)
In a quantitative field research, the objective of this work was to determine the best stocking density for tambatinga juveniles (Colossoma macropomum × Piaractus brachypomus) in a recirculation system during 50 days of cultivation. Tambatinga juveniles (0.72±0.02 g) were distributed in 0.08 m3 polyethylene boxes with densities of 5, 10 and 15 fish/box, with five replicates per treatment. During the experimental period, water quality, weight gain, apparent feed conversion, specific growth rate, carcass yield, proximate composition and final survival were evaluated. The water parameters remained stable and in the desired range for the species during the experimental period (temperature 25±1.52° C, pH 5.85±0.7 and dissolved oxygen 6.51±0.05 mg L-1). Statistical analyzes showed no significant difference for apparent feed conversion and survival rate. The lowest stocking density (5 fish/box) showed greater weight gain and specific growth rate, while the density of 10 fish/box showed high lipid deposition in the carcass. Aiming at greater weight gain and better specific growth rate, the results indicated that the density of 5 fish/box (0.08 m3), is the most suitable for juveniles of this species.